Mechanical and metallurgical properties of DP 1000 steel square butt welded joints with GMAW - Rocha, Ianto; Machado, Ivan; Mazzaferro, Cintia (International Journal of Engineering and Technology, 2014)
In this work, Gas Metal Arc Welding (GMAW) was used to study the influence of heat input (i.e. cooling rate) on mechanical/metallurgical properties of square butt welded joints of DP 1000 sheets. The influence of filler metals of different strengths on the mechanical properties of joints was also tested. A significant decrease in hardness was observed in the Heat Affected Zone (HAZ) due to martensite tempering, in regions where peak temperature was close to isotherm AC1 (calculated in 735 oC for these steel); coincidently, fracture in every tensile test occurred in regions where martensite was tempered, even when a wire of less strength was used. It was noticed that the decrease in ultimate tensile and yield strength of base metal was inherent to welding. When minimum heat input was used, deterioration in mechanical properties was less pronounced, once degree of HAZ softening was smaller. Elongation of joints increased with increasing heat input.